Getting the forecast right. - Holman, Tom (Bookseller)
The article reports on the improvements in accuracy of book selling forecasting. Using historical data and trends Nielsen BookScan has given publishers a more accurate record of how many copies are selling. As BookScan's data becomes more sophisticated, forecasting software systems for publishers are also being improved. International Business Systems (IBS) integrates point-of-sale figures and publishers' records. Data sharing, print-on-demand, and wholesalers are discussed.